FORMATION OF KEY COMPETENCIES OF EDUCATION SEEKERS IN CONDITIONS OF BLENDED LEARNING - Iryna Lovyanova; Oleksii Kozachenko; Andriy Krasnoshchok (Alfred Nobel University Journal of Pedagogy and Psychology, 2025)
The presented work substantiates the peculiarities of the formation of key competencies of education seekers in conditions of blended learning. We analysed this problem in the scientific literature in the following directions: A. the specifics of forming and developing a competent personality at various educational levels; B. scientific approaches to understanding the essence of blended learning; C. the characteristics of blended learning from a competency-based approach in education. The purpose of the article is to study methodological approaches to the formation of the key learning- to-learn competence in high school students and to develop pedagogical support for higher education students in acquiring self-educational competence under blended learning conditions. The following research methods were used: content analysis of regulatory legal acts in the field of education; analysis, generalization, and specification of scientific-pedagogical and methodological sources regarding the formation of a competent personality of education seekers at various levels in blended learning environments; surveys of teachers and education seekers on their attitude towards the use of blended learning technologies to develop students’ ability to learn and the self-educational competence of university students. It was found that such key competencies as the ability of school students to learn and the self- educational competence of students are essential for achieving educational success, especially in blended learning conditions. The authors researched the possibility of developing the key learning-to-learn competence in high school students, conditioned by their psychological readiness for self-education and self- development at this age. The study developed and implemented an elective course titled “Fundamentals of Cognition in Learning” within the educational process; a platform for organizing blended learning for high school students was proposed, along with methodological recommendations for teachers on how to provide pedagogical support to students in blended learning environments to foster their competencies. The advantages of blended learning in organizing the independent work of university students and developing their self-educational competence are highlighted – particularly through online learning using learning management systems, such as LMS Moodle. The analysis of respondents’ answers helped to set methodological focuses in organizing learning activities in an online course. The authors of the study propose identifying the following key stages of the course, which ensure support for learners: familiarization with the course, its purpose and objectives; weekly learning planning; introduction to theoretical materials; completion of practical tasks; taking tests; and communication with instructors and fellow participants. It was found that compliance with the conditions for using online courses in blended learning contributes to the effective formation of students’ self-educational competence. Conclusions. The conducted research substantiates the importance of developing key competencies in learners, such as the ability to learn and self-educational competence of university students. To ensure the effective formation of this competence, an elective course for high school students titled “Fundamentals of Cognition in Learning” was developed, along with a proposal to integrate it into the information and educational environment of secondary education institutions using Google cloud services. A comprehensive analysis of the development of blended learning for higher education students demonstrates its significant potential in forming students’ self-educational competence. Participation in online courses increases motivation to learn, fosters self-control and reflection, and develops teamwork skills.